2011
DOI: 10.1111/j.1742-7843.2011.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein and DNA Oxidation in Different Anatomic Regions of Rat Brain in a Mimetic Ageing Model

Abstract: It has been reported that D-galactose administration causes an increase in oxidative and osmotic stresses in several tissues of rodents. In this study, we established a brain ageing model by using D-galactose and investigated the concentrations of oxidative stress markers on the hippocampus, parietal and frontal lobes of male Sprague-Dawley rats. A mimetic ageing model was established by injecting D-galactose (60 mg ⁄ kg ⁄ day ⁄ i.p.) in the experimental group for 42 days. At the end of this period, we tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 58 publications
1
41
0
Order By: Relevance
“…Therefore, understanding the causes and mechanisms associated with age‐related cardiovascular diseases is of considerable importance. Many experimental indications have shown that the characteristics of premature ageing induced by chronic d ‐galactose exposure are similar to those in natural ageing in rodents . Galactose is a monosaccharide sugar, and although it has two forms, the d and l forms, the body can metabolize only the d form of galactose.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, understanding the causes and mechanisms associated with age‐related cardiovascular diseases is of considerable importance. Many experimental indications have shown that the characteristics of premature ageing induced by chronic d ‐galactose exposure are similar to those in natural ageing in rodents . Galactose is a monosaccharide sugar, and although it has two forms, the d and l forms, the body can metabolize only the d form of galactose.…”
Section: Introductionmentioning
confidence: 99%
“…15 Other advantages are the easy application, low incidence of tumors, and the high survival rate of the animals throughout the experimental period. 16,17 It is important to note that, more recently, some dissonant reports concerning the effectiveness of this accelerated aging paradigm have been published. [18][19][20] Indeed, Parameshwaran and collaborators have concluded that the d-galactose treatment (intraperitoneal [i.p] injection of 100 mg/kg per day) in female C57BL/61 mice was not suitable for testing antioxidant compounds in mice.…”
Section: Introductionmentioning
confidence: 99%
“…17,24 We focused the present study on the hippocampal formation (HF), a brain limbic region particularly affected by aging [25][26][27][28][29] and presenting the hallmarks of neuronal agerelated deterioration. 14,16 Furthermore, because d-galactose may interfere with neurogenesis, 9,30 we decided to analyze the effects of the high-dose d-galactose on the neurogenesis of the hippocampal dentate granule cells using two neurogenic markers, doublecortin (DCX) and Ki-67, that are easily quantified in young rodents. 11,21 The focus on the neurogenic process assumes importance because new neurons can replace those lost through pathological or physiological events in the adult rodent brain, 31 but this capacity decreases with aging.…”
Section: Introductionmentioning
confidence: 99%
“…This sugar is commonly used in our daily life as table sugar. The root mechanism of aging process is still unclarified due to difficulties in performing experimental aging studies such as ethic problems, cost, time, and age‐related additional pathologies (Yanar et al, ). In order to solve these problems, researchers directed their researches on model organisms such as Caenorhabditis elegans , Mus musculus , Saccharomyces cerevisiae , Danio rerio, and D. melanogaster (Pandey & Nichols, ).…”
Section: Introductionmentioning
confidence: 99%